EMPIRICAL ANALYSIS OF LEGAL PROTECTION AND DEFAULT DETERMINANTS IN CONSTRUCTION CONTRACTS: A CASE STUDY OF PT. DASH LEBANG PERKASA - Zulfikar Andi Makmur; Sarjiyati Sarjiyati; Taufiq Yuli Purnama (Sharia Oikonomia Law Journal, 2026)
The construction industry plays a strategic role in national infrastructure development, yet service providers often face legal vulnerabilities due to imbalanced contractual relationships with project owners. This study aims to analyze the forms of legal protection afforded to construction service providers and to identify the determinants of default (wanprestasi) in construction work contracts, with PT. Dash Lebang Perkasa as the case study. Employing an empirical legal research design (normative-empirical), this study utilizes a statute approach and a conceptual approach, drawing on primary legal materials, secondary literature, and empirical field data spanning from 2019 to 2025. The findings reveal that legal protection operates through three interconnected dimensions: regulatory-substantive protection grounded in the Indonesian Civil Code and Law Number 2 of 2017 on Construction Services; contractual protection through meticulously drafted clauses on payment mechanisms, variation orders, force majeure, and retention funds; and procedural protection fortified by the company's legal transformation from a partnership (CV) to a Limited Liability Company (PT) in 2023. Meanwhile, default determinants are multi-causal, encompassing internal factors (time management, human resource limitations, insufficient capital buffers, and logistics weaknesses) and dominant external factors, particularly delayed milestone payments by project owners that paralyze operational cash flow. This study contributes to construction law literature by offering a comprehensive framework for equitable contractual risk management.